(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
Beliefs about emotions may affect individuals’ emotional experiences and well-being. This research tested the assumption that specific beliefs about emotions, particularly beliefs about valuing positive emotions may be associated with individual happiness and satisfaction. 200 participants filled out a questionnaire examining beliefs about valuing positive emotions, affect, individual happiness and life satisfaction. Results revealed that beliefs about valuing positive emotions significantly predicted happiness and life satisfaction. Also, the link between belief about valuing positive emotions and individual happiness and the link between beliefs about valuing positive emotions and life satisfaction were partially explained by positive affect. These findings suggest the importance of examining individuals’ beliefs about valuing positive emotions and the experience of positive emotions together for individuals’ well-being.